Pengaruh edukasi motivational interviewing terhadap efikasi, pengetahuan, perubahan perilaku pada masalah kesehatan anak: Tinjauan sistematik - Setiawati, Atik; Rahmadhani, Dewi Astika; Rustina, Yeni; Hayati, Happy; Huda, Mega Hasanul (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The implementation of child care education will be different from adult care education. This is because children are not miniature adults. However, the role of child care cannot be separated from the involvement of parents or families. Motivational interviewing (MI) educational interventions have been suggested to improve efficacy, knowledge, and health behavior change in pediatric patients. Psychological approaches such as Motivational Interviewing (MI) have emerged as a promising alternative to overcome these limitations, with the aim of creating more sustainable behavior change in the context of health. Purpose: To evaluate the impact of Motivational Interviewing (MI)-based education on efficacy, knowledge, and behavioral change in children. Method: A systematic literature review study using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and the PICOS approach. The keywords used were,